Mafic intrusions in southwestern Australia related to supercontinent assembly or breakup?. Issue 2 (17th February 2022) - Olierook, H. K. H.; Jourdan, F.; Kirkland, C. L.; Elders, C.; Evans, N. J.; Timms, N. E.; Cunneen, J.; McDonald, B. J.; Mayers, C.; Frew, R. A.; Jiang, Q.; Olden, L. J.; et al.
Abstract: Variably oriented dolerite intrusions outcrop in the Albany–Fraser Orogen along the south coast of Western Australia with previously unknown ages but where previous studies interpreted Mesoproterozoic to Cretaceous emplacement. Here, we place temporal constraints on seven mafic intrusions across ∼150 km of coast using zircon U–Pb, apatite U–Pb, and plagioclase 40 Ar/ 39 Ar geochronology, coupled with whole-rock major and trace-element geochemistry, that reveal late Mesoproterozoic to potentially Early Cretaceous crystallisation ages. Three intrusions metamorphosed to greenschist facies are likely associated with either the emplacement of the ca 1210 Ma Marnda Moorn large igneous province or Stage II Albany–Fraser Orogeny, both of which were associated with the assembly of Rodinia. Three unmetamorphosed dykes have (probable) Neoproterozoic to lower Cambrian emplacement ages, likely associated with the ca 550–500 Ma Kuunga Orogeny during Gondwana assembly. The final sill, also unmetamorphosed, strikes perpendicular to the other six intrusions, shows unusual Pb anomalies and contains inherited zircon that has been reset by a Permian or younger event, pointing towards magmatism in southwestern Australia during the breakup of Gondwana. The new results provide hitherto unrecognised mafic intrusive evidence for modification of Proterozoic crust, potentially associated with Rodinia assembly, Gondwana assembly and Gondwana breakup in southwestern Australia. KEY POINTS: Variably oriented mafic dykes in southwest Australia are dated by zircon U–Pb, apatite U–Pb and plagioclase 40 Ar/ 39 Ar methods. The dykes are related to Rodinia assembly ( ca 1200 Ma), Gondwana assembly ( ca 550 Ma) and, probably, Gondwana breakup ( ca 135 Ma). These new ages provide evidence for mafic activity clearly linked to the supercontinent cycle.